2014
DOI: 10.1158/0008-5472.can-14-0013
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Cancer Cell Lines Are Representative Models of the Main Molecular Subtypes of Primary Cancer

Abstract: Human colorectal cancer cell lines are used widely to investigate tumor biology, experimental therapy, and biomarkers. However, to what extent these established cell lines represent and maintain the genetic diversity of primary cancers is uncertain. In this study, we profiled 70 colorectal cancer cell lines for mutations and DNA copy number by whole-exome sequencing and SNP microarray analyses, respectively. Gene expression was defined using RNA-Seq. Cell line data were compared with those published for primar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
269
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 331 publications
(297 citation statements)
references
References 44 publications
(43 reference statements)
17
269
0
Order By: Relevance
“…Several studies show that CRC cell lines recapitulate the main molecular phenotypes observed in primary CRC (Ahmed et al ., 2013; Barretina et al ., 2012; Berg et al ., 2017; Medico et al ., 2015; Mouradov et al ., 2014), which substantiate their value as preclinical model systems to assess a variety of pharmacogenomic relationships. Consistent with the observed clinical benefit in patients with CDX2‐negative tumors in stage III, loss of CDX2 expression was strongly associated with sensitivity to conventional chemotherapeutics in vitro , both in our drug screen dataset and in a large public dataset, again independent of MSI status.…”
Section: Discussionmentioning
confidence: 73%
“…Several studies show that CRC cell lines recapitulate the main molecular phenotypes observed in primary CRC (Ahmed et al ., 2013; Barretina et al ., 2012; Berg et al ., 2017; Medico et al ., 2015; Mouradov et al ., 2014), which substantiate their value as preclinical model systems to assess a variety of pharmacogenomic relationships. Consistent with the observed clinical benefit in patients with CDX2‐negative tumors in stage III, loss of CDX2 expression was strongly associated with sensitivity to conventional chemotherapeutics in vitro , both in our drug screen dataset and in a large public dataset, again independent of MSI status.…”
Section: Discussionmentioning
confidence: 73%
“…We also observed that the rare hypermutator/ MSI-negative subgroup, identified in about 2% of CRC cases, is represented by three lines, HT115, HCC2998 and HT55 (ref. 16). …”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, precision oncology depends on the ability to functionally interrogate preclinical models capturing the molecular heterogeneity observed in patients. While collections of cancer cells derived from multiple tumor types have been previously described 1,2,4 , comprehensive databases of cells derived from single tumour lineages are much less common 16,31 . To capture the clinical heterogeneity of CRCs, we assembled a collection of 151 cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…4A). Interestingly, the T173I mutation was found in RUNX3 in the colon carcinoma cell line LS411, whereas its equivalent mutation in RUNX1 (T196I) was detected in chronic myelomonocytic leukemia (cancer.sanger.ac.uk/cosmic) (23)(24)(25); the equivalent residue in RUNX2 was found to be mutated, also to isoleucine, in the disease cleidocranial dysplasia (CCD) (26). This finding indicates that the T173 residue is important for the function of the Runt domain.…”
Section: Mutation Of T173 Results In Impairment Of Dna Binding and Trmentioning
confidence: 99%